Decoding the Dining Atmosphere: Ambient Conditions and Customer Satisfaction in Restaurant Servicescapes - Ray, Nilanjan; Lama, Pema; Majumder, Tanmoy; Roy, Moumita (ASEAN Journal on Hospitality and Tourism, 2025)
This study investigates the effects of ambient conditions, one of the essential dimensions of the Servicescape Model, on restaurant customer satisfaction. Ambient conditions like lighting, music, scent, and temperature are extremely influential in shaping customer feelings and perceptions. Based on Bitner's Servicescape and the Stimulus-Organism-Response (S-O-R) model, the study collected data from 230 survey participants in Indian urban restaurants. Using descriptive statistics, correlation matrices, and multiple regression analysis, the research determines scent and lighting to be strong predictors of satisfaction, then music. Temperature, although applicable, failed to show a statistically significant effect. Results of the findings provide practical implications for optimizing service environments in the hospitality industry.